Carbonization of Coconut Shell Biomass in a Downdraft Reactor: Effect of Temperature on the Charcoal Properties - Ahmad, R.K. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Considering the value of coconut shell biomass as renewable fuels in homes and commercial industries, its effectiveness as a biomass resource has been overlooked by our rural citizens and researchers. Carbonization experiments of coconut shell biomass were conducted in a downdraft carbonization reactor (750 mm height and 67 mm diameter) to determine the effect of temperature (250 to 600°C, in 50°C intervals) on the charcoal properties. This was to address the problems of traditional charcoal production methods that include; low yield, environmental pollution, unregulated temperature, and poor quality properties. Yet the scarcity of this information hampers efforts for efficient commercial production. The coconut shell biomass was obtained from a local shop in Malaysia. It was heated in the reactor at a fixed residence time of 60 min and a particle size of 5 mm with nitrogen as a carrier gas. The relationship between temperature and the properties of coconut shell charcoal has been ascertained by the findings of this analysis. The relatively high the temperature, the better the charcoal quality, but the lowest the charcoal yields, since the secondary pyrolysis reaction expends charcoal. It was noted that, up to a final temperature of 500°C, the yield reduction was rapid; after that, it was slower at 550°C and almost stable at 600°C. According to the charcoal's proximate analysis, the calorific value, fixed carbon content, carbon content and ash content increased with temperature. Whereas, the charcoal density, volatile matter, moisture content, and conversion efficiencies decrease with temperature. The presence of nitrogen gas appears to have reduced combustion reactions that promote the formation of carbon dioxide (CO2). The methods produce the least amount of air pollutants (96 g carbon monoxide (CO), 167 g CO2, and 64 g methane (CH4) per 1 kg of charcoal production). The type of biomass and carbonization kiln has an impact on the production of CO, CO2, and CH4. Thus, the carbonization reactor used in this study has the potentials to produce an eco-friendly charcoal with superior quality properties that can assist in reducing environmental pollution, by proper selections of carbonization temperature. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.